Consumer Perceptions of Transaction Security in Digital Marketplaces - Cece Harahap (Digital Innovation : International Journal of Management, 2025)
This study aims to explore consumer perceptions regarding transaction security on digital marketplaces and to evaluate the impact of community-based educational interventions. A descriptive qualitative method was employed, involving in-depth interviews with ten active marketplace users in Tasikmalaya City. The findings revealed that consumers’ sense of security is shaped by personal experience, understanding of platform security features, and digital literacy. Prior to the intervention, most participants expressed high concern over data breaches and fraud, often opting for cash-on-delivery (COD) as a form of protection. Following a series of community education sessions—comprised of discussions and safe transaction simulations—significant changes were observed in consumer attitudes and behavior. Participants became more aware of the importance of verifying sellers, reading reviews, and using secure payment methods. The study concludes that localized community education effectively enhances awareness and trust among consumers, especially in areas where digital literacy remains limited.